International Trade, Factor Mobility and Trade Costs. - Norman, V; Venables, A (CEPR, 1993)
We consider a Heckscher-Ohlin model in which goods and factors of production can be traded, but trade involves transactions costs. Goods trade alone will not equalize factor prices, so there is an incentive for trade in factors of production. Whether goods or factors are traded depends on endowments and transactions costs. We characterize equilibria in which there is no trade, there is goods trade only, there is factor trade only, and there is trade in both goods and factors. This generalizes the Heckscher-Ohlin model to explain not only the direction of trade, but also the prior question of how goods and factors are partitioned to tradables and non-tradables.